2022
DOI: 10.3389/fimmu.2022.772446
|View full text |Cite|
|
Sign up to set email alerts
|

Glucagon-Like Peptide-1 Receptor Regulates Macrophage Migration in Monosodium Urate-Induced Peritoneal Inflammation

Abstract: Glucagon-like peptide-1 (GLP-1) is an insulinotropic peptide that signals through the GLP-1 receptor (GLP-1R). GLP-1R, therefore, plays a critical role in diabetes and cardiovascular disease. Whether GLP-1R is involved in inflammatory disease such as gout remains unclear. Macrophages are critical effector cells in the pathogenesis of gout, a common form of inflammatory arthritis caused by the deposition of uric acid in joints. The expression of GLP-1R at the protein level is controversial due to the lack of sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…Notably, we found that consumption of LYP promoted the expression of GLP-1 in the small intestine. Emerging evidence has suggested that GLP-1 could enhance intestinal barrier function and regulate macrophage polarization. , Consistent with the reported study, our results verified that LYP intervention remarkably up-regulated the expression of GLP-1, promoted polarization of M2, and protected the intestinal barrier function. However, additional studies are needed to clarify the detailed mechanism underlying the effects of LYP on GLP-1 secretion and expression.…”
Section: Discussionsupporting
confidence: 92%
“…Notably, we found that consumption of LYP promoted the expression of GLP-1 in the small intestine. Emerging evidence has suggested that GLP-1 could enhance intestinal barrier function and regulate macrophage polarization. , Consistent with the reported study, our results verified that LYP intervention remarkably up-regulated the expression of GLP-1, promoted polarization of M2, and protected the intestinal barrier function. However, additional studies are needed to clarify the detailed mechanism underlying the effects of LYP on GLP-1 secretion and expression.…”
Section: Discussionsupporting
confidence: 92%
“…Novel findings regarding the basic biochemistry/biology of UA in the context of gout published over the past year were not abundant but do include a report demonstrating a role for glucagon-like peptide-1 (GLP-1) and its receptor GLP-1R in the inflammatory response to monosodium urate crystals [16]. This study demonstrated GLP-1R expression in murine macrophages with greater expression in M2 and Ly6C+ macrophages than their corresponding counterparts.…”
Section: Ua and Goutmentioning
confidence: 96%
“…The expression of GLP-1R remains controversial due to the lack of specific antibody against GLP-1R, with most of the literatures using qPCR to detect mRNA levels ( 24 , 25 ). There were also a few studies detected the expression of GLP-1R at the protein level using a lineage-tracking animal model ( 26 , 27 ). Although Glp1r mRNA transcripts have been detected in murine lymphoid tissue, little is known about the role of GLP-1 in the immune system ( 28 ).…”
Section: Introductionmentioning
confidence: 99%